Analisis Jumlah Pekerja Migran Indonesia (PMI) dan Remitansi terhadap Tingkat Kemiskinan di Kabupaten Ponorogo - Bimantara Dwi Setyaji; Ririt Iriani Sri Setiawati (IPM2KPE, 2023)
This research aims to determine the influence of the number of Indonesian Migrant Workers (PMI) and Remittances on poverty levels in Semarang Regency. The analytical method used is multiple linear regression analysis using the help of E-views 12 software. The results of the research show that the number of Indonesian Migrant Workers (PMI) has a positive and significant effect on the poverty level in Ponorogo Regency. Meanwhile, remittances have a negative and significant effect on poverty levels in Semarang Regency. Keywords: Indonesian Migrant Workers, Remittances, Poverty Level